IMPLEMENTING PROTOTYPE METHOD FOR ELECTRONIC PAYMENT FACILITY OF CERTIFICATE SERVICING SYSTEM IN MAA TAKAFUL - Priya Kasi, 1979-, author; Othman Mohd. Yusop, supervisor; Sekolah Informatiks Termaju (Kuala Lumpur : universiti Teknologi Malaysia, 2015)
Thesis (Sarjana Kejuruteraan Perisian)-Universiti Teknologi Malaysia, 2015